Buku Cerita Interaktif Tentang Ikan Kembung Sebagai Sumber 0mega-3 Balita Di Kota Palembang - Nugraha, M. Ihsan; Yulius, Yosef; Mubarat, Husni (Penerbit dan Percetakan, CV. Picmotiv, 2024)
The First Thousand Days of Life (HPK) is a crucial period in a child's development. Several factors influence this process, including physical, social, emotional, and cognitive aspects. During this time, a child's brain can form a thousand new neural connections every second. Between the ages of two and six, there is rapid growth in the brain regions responsible for cognitive abilities. Nutrition that affects cognitive development in children includes omega-3, a nutrient found in foods such as mackerel. However, fish is less popular among children. The reasons children dislike fish include its fishy smell and a lack of understanding about the nutritional benefits of fish, especially mackerel, by their parents. This issue can be addressed through the knowledge of Visual Communication Design, which plays an important role in creating interactive storybooks that can encourage parents and children to better understand and consume mackerel as a source of omega-3.